Pengaruh Kepemimpinan Partisipatif, Disiplin Kerja, Motivasi, terhadap Kompetensi Profesional Guru di SMP Swasta Budi Utomo Binjai - Dewi Andayani; Elfrianto Elfrianto; Akrim Akrim (Journal Of Administration and Educational Management (ALIGNMENT), 2022)
ABSTRAK This study aims to determine the effect of participatory leadership, work discipline, and motivation, on the professional competence of teachers at Budi Utomo Binjai Private Junior High School. The sample in this study were all 53 teachers at Budi Utomo Binjai Private Junior High School. This study used a questionnaire as primary data and then the data results were analyzed using multiple regression by conducting a stimulant test, determination test, and partial test with a significant level of 5 percent (α = 0.05) which was processed with the help of SPSS 22. The results of this study are there is a positive and significant influence of participatory leadership, work discipline, and motivation on the professional competence of teachers at Budi Utomo Binjai Private Junior High School as seen through the results of the stimulant test with an F count of 11.534 and probability value or p-value = 0.000 <0.05. The results of the partial test show that participatory leadership has a positive and significant effect of 0.000 and t count of 109.843, work discipline has a positive and significant effect of 0.000 and t count of 117.936, motivation has a positive and significant effect of 0.000 and t count of 115.386. positive participatory leadership, work discipline, and motivation on the professional competence of teachers. Keywords: Work Discipline, Participatory Leadership, Teacher Professional Competence, Motivation